The Influence of Leadership Style, Motivation, and Stress on the Performance of Denpasar Public Library Employees - Ni Ketut Ayu Maharani MAHARANI; A.A. Ketut JAYAWARSA; N. PARAMANANDA (Loka: Journal Of Environmental Sciences, 2023)
Purpose:This research aims to test and analyze the influence of leadership style, work motivation and work stress on employee performance.Methodology:This research was conducted at the Denpasar City Public Library with a research sample of 37 respondents taken using the saturated census technique. All data obtained from the questionnaire distribution is suitable for use, then analyzed using multiple linear regression and hypothesis testing (t-test and f-test).Findings:The research results show that (1) Leadership style, work motivation and work stress have a positive and significant effect on employee performance at the Denpasar City Public Library, (2) Leadership style has a positive and significant effect on employee performance at the Denpasar City Public Library. It means that the better the leadership style, the greater the employee performance at the Denpasar City Public Library. (3) Work motivation positively and significantly affects employee performance at the Denpasar City Public Library. It means that the more work motivation increases, the greater the performance of employees at the Denpasar City Public Library (4). Work stress negatively affects employee performance at the Denpasar City Public Library.Implication:It means that the greater the work stress, the lower the employee performance at the Denpasar City Public Library.